Voisins ou ennemis à Arba Wa Nus ? La mise en scène du quotidien des migrants forcés égyptiens et réfugiés sud soudanais dans un quartier populaire du Caire - Fabienne Le Houérou (Revue des Mondes Musulmans et de la Méditerranée)
Based on video filming used as a research tool and influenced by the sociology of interactions, this article seeks to explore the relations between two displaced populations in Cairo (South Sudanese and Egyptians from Upper Egypt) in an outlying zone of the megalopolis. Observing the presentation of self in everyday interactions in public places in the Arba Wa Nus quarter, prompts us to propose the hypothesis of a territory essentially “marked” by social violence. Can we say that the aggressions of which the South Sudanese are victims are the sign of the emergence of a “new racism”, related to the influx of forced migrants from Africa to Egypt? Are everyday hostilities a sui-generis social product of a marginal space which could be characterized by poverty and by the uprooting of the populations living there? Those are the two questions we attempt to answer here.